Perbandingan Penggunaan Cairan Pendingin Radiator Terhadap Temperatur Kerja Mesin Mobil Toyota Avanza 1.5 S M/T - Haris Haris; Nota Effiandi; Asmed Asmed (Jurnal Teknik Mesin, 2022)
The increasing economic growth of the Indonesian people has implications for the number of vehicle ownership, especially cars. However, this increase is not matched by public understanding of the need for maintenance of the engine cooling system. One way that can be done is to use radiator coolant to maintain the cooling system so that engine performance remains in optimal condition. The purpose of this study was to determine and compare the working temperature of the engine when using several types of radiator coolant. This research uses an experimental approach research method. The test was carried out at 750 RPM, 1500 RPM, 3000 RPM and using a coolant containing a mixture of water with ethylene glycol 0%, 30%, 50% and 80%. In the calculation, it is found that the working temperature of the Toyota Avanza 1.5 M/T car engine is very good using a mixture of water and ethylene glycol 50%, namely with an average engine working temperature of 94.8℃, then a mixture of water and ethylene glycol 30%, namely with an average temperature engine working 96.3℃, a mixture of water and ethylene glycol 80%, with an average working temperature of 98.6℃ engine and a mixture of water and ethylene glycol 0%, with an average working temperature of 101.5℃